1999
DOI: 10.1021/ma981794t
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Characterization, and Expansion of Poly(tetrafluoroethylene-co-hexafluoropropylene)/Polystyrene Blends Processed in Supercritical Carbon Dioxide

Abstract: Poly(tetrafluoroethylene-co-hexafluoropropylene) (FEP)/polystyrene blends were prepared by the heterogeneous free-radical polymerization of styrene in supercritical (SC) CO2-swollen FEP substrates. Volume incorporations of up to 50% polystyrene were achieved, and the composition and phase morphology of the blends were controlled by varying the styrene monomer concentration and reaction time. The crystallinity and glass transition temperature of the FEP substrate are unaffected by the addition of the polystyren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
66
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(69 citation statements)
references
References 18 publications
3
66
0
Order By: Relevance
“…The crystallinity of the virgin polymer in this case is around 41.38%, using 92.94 J/g as the enthalpy of fusion for 100% crystalline FEP. 31 This value is very similar to that observed in the samples processed with and without CO 2 (40.37 and 37.0%, respectively), and it appears not to be affected in a significant way by the melting process. This general behavior is a consequence of the inherently larger processability of FEP that, despite the high molecular weight, does not restrict the recrystallization process, so that most of the crystallinity in the sample can be recovered after melting.…”
Section: Fluorinated Ethylene Propylene Copolymer (Fep)supporting
confidence: 83%
“…The crystallinity of the virgin polymer in this case is around 41.38%, using 92.94 J/g as the enthalpy of fusion for 100% crystalline FEP. 31 This value is very similar to that observed in the samples processed with and without CO 2 (40.37 and 37.0%, respectively), and it appears not to be affected in a significant way by the melting process. This general behavior is a consequence of the inherently larger processability of FEP that, despite the high molecular weight, does not restrict the recrystallization process, so that most of the crystallinity in the sample can be recovered after melting.…”
Section: Fluorinated Ethylene Propylene Copolymer (Fep)supporting
confidence: 83%
“…18 In the solid state, supercritical CO 2 plasticization has been employed to enhance the solubility of styrene in poly(tetrafluoroethylene-cohexafluoropropene) followed by in situ polymerization of styrene to thereby produce polymer-polymer composites. 19 Compressed CO 2 was found to facilitate the crystallization of methyl-substituted poly(aryl ether ether ketone) and tert-butyl-substituted poly(ether ether ketone) (tBuPEEK), which normally do not undergo crystallization upon annealing. 20,21 Related to these applications are investigations of CO 2 polymer plasticization, with most studies focusing on amorphous polymers.…”
Section: Introductionmentioning
confidence: 99%
“…[210] Recall that blend compositions can be tuned by controlling parameters such as the exposure and reaction times, CO 2 pressure, temperature, and monomer/initiator concentrations. [203,207,[211][212][213] A decisive consideration here is that the blend composition is not limited by the solubility of the monomer in the fluid or matrix phase, since polymerization depletes the monomer reservoir and permits more than the equilibrium concentration of the monomer to penetrate into the polymer substrate. [201,202,207,214,215] The resulting blends can be further modified through additional chemical means such as chemical crosslinking and surface sulfonation; [201] alternatively, the polymerization can be restricted to the substrate surface, thereby yielding a grafted surface layer.…”
Section: Impregnation Polymerizationsmentioning
confidence: 99%
“…In one case, it has been observed that grafting poly(acrylic acid) (PAA) to iPP does not lead to any discernible changes in T m and the crystallinity of the iPP substrate (since the grafting reaction is limited to amorphous iPP regions). [212] Although the crystal structure of the substrate polymer remains largely unaffected by the incorporation of grafted chains, [202,211] accompanying reductions in T m have been reported. [216] Morphological analysis [202] of CO 2 -impregnated polymer blends reveal that polymerized PS resides in amorphous regions of HDPE, as well as throughout existing spherulites (Fig.…”
Section: Impregnation Polymerizationsmentioning
confidence: 99%